PERBANDINGAN EFEKTIVITAS POVIDONE IODINE 10% DAN EKSTRAK ETANOL DAUN COCOR BEBEK (KALANCHOE PINNATA) TERHADAP LAMA PENYEMBUHAN LUKA BAKAR PADA TIKUS PUTIH (RATTUS NORVEGICUS L.) JANTAN GALUR WISTAR - M. HATADI ARSYAD; ERY SUHAYMI (LP2MTBM MAKARIOZ, 2021)
Burns are a form of trauma to the skin or other tissues caused by heat, ultraviolet radiation, electromagnetic energy, electricshock or contact with hazardous chemicals. Burns often have adverse effects on humans both physically and psychologically.The process of healing burns includes the phases of hemostasis, inflammation, proliferation, and tissue remodeling.Povidone iodine has strong antimicrobial properties. The criteria that must be met for a good dressing is to maintain highhumidity between the wound and dressing. Kalanchoe pinnata are rich in flavonoids, bufadienolides, and saponins. To findout the effectiveness of 10% povidone iodine and ethanol extract of Kalanchoe pinnata on the healing time of burns in Rattusnorvegicus L. This study is a true experimental study with a post test controlled group design. In terms of the average rate ofhealing of burns, povidone iodine 10% has the fastest time of 7 days followed by ethanol extract of Kalanchoe pinnata 11days and control 12 days. In terms of effectiveness, povidone iodine is 10% more effective than ethanol extract of Kalanchoepinnata and controls in healing burns. Povidone iodine is 10% more effective than ethanol extract of Kalanchoe pinnata inhealing burns in Rattus norvegicus L. Ethanol extract of Kalanchoe pinnata can be considered as an alternative to healingburns.